Park Landscapes And The Formation Of Their Visual Environment - Kurbanov Sh.M (Researchparks Publishing, 2022)
The regularities of the formation of the visual environment of the recreational areas of the city, based on the theory of saccade automation and video ecological parameters of the visibility basin, are considered.